Totally laparoscopic resection of a rare duodenal tumour. (30th May 2012) - Hadjittofi, Christopher; Parisinos, Constantinos A; Somri, Mostafa; Matter, Ibrahim
Abstract : A 39-year-old woman presented to the gastroenterology clinic with recurrent right-upper-quadrant pain and elevated liver enzymes. Endoscopy revealed a small submucosal mass at the edge of the major duodenal papilla, which was not amenable to endoscopic resection. The mass was successfully resected by laparoscopy. The papilla was subsequently reconstructed and a cannula inserted in the common bile duct. The postoperative period was uneventful and the patient was discharged on the third postoperative day. Subsequent pathological examination of the excised mass revealed a gangliocytic paraganglioma. Six weeks later, the patient was free of symptoms and the cannula was removed by duodenoscopy.